Discovering the Experience of Financial Technology (FinTech) Users in Paying Zakah, Infaq, and Sadaqah (ZIS) in East Java, Indonesia - Dwi Agustiningsih, Maulida; Islami, Novita Nurul; Tiara, Tiara; Pramono, Widyo (LPPM Universitas Terbuka, 2021)
COVID-19 impacts the people and some companies in different sectors. This pandemic creates online Zakah, Infaq, and Sadaqah (ZIS) payments which must be developed in line with FinTech services in Indonesia that increase continuously. However, many companies lack intentions on User Experience (UX) that can be a risk for services or products. This study explores the Experience of Financial Technology (FinTech) users in Paying Zakah, Infaq, and Sadaqah (ZIS). The quantitative method is used by collecting online questionnaires through FinTech users in East Java, Indonesia. PLS-SEM was used to analyze data. Findings. The result indicated that both information and system quality have no impact on the user experience. Meanwhile, service quality positively relates to user experience. As a result, this study disclosed the user experience of ZIS payment during COVID-19 that will lead to the user's intentions and net benefit.